IR and Uv-Visible Study of the Thermal Stabilization for pvc Stabilized with ( Ho,Tb and Dy ) Stearate and Synergistic Mixtures - Al-Huseini, H. A. M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Three  types of  metal  carboxylates  (Ho,Tb  and  Dy) stearates were LLSed  as thennal stabi lizers for PVC. Infrared spectra (1500-1900 ) cm.1 were   studied   for  PVC   films   stabilized   with   these   metal carboxylatcs.  Two types of oxygen  were round -containing  products that were formed during  the thermal degradation  .On the other hand , the  presence  of  atmospheric  oxygen  leading  to  the  formation   of carbonyl  groups  on  the  chain  seems   to  play  a  great   role  in  the stabilization of PVC.It was found that IR spectroscopy was suitable to follow the consumption  of the carboxylatcs  within the thermal  stress periods via antisymmetrical  stretching  vi bration of COO. The thermal stability ior  the PVC in present of synergistic mixtures (Ho-Tb,Ho-Dy and Tb-Dy)  stemÂ·ates was studied  by U l traviolet-visi ble spectra.The results indicate that these mixtures have considerable stabilization efficiency for the PVC.